Application of the renormalization group in many-body quantum mechanics - Van der Ventel, B. I. S.(Brandon Izak Samuel) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1995.